Non-invasive, targeted, and non-viral ultrasound-mediated brain-derived neurotrophic factor plasmid delivery for treatment of autism in a rat model - Shen, Yuanyuan; Li, Nana; Sun, Shuneng; Dong, Lei; Wang, Yongling; Chang, Liansheng; Zhang, Xinyu; Wang, Feng (Frontiers in Neuroscience, 2022)
Autism has clinical manifestations such as social interaction disorder, speech and intellectual development disorder, narrow interest range, and stereotyped and repetitive behavior, all of which bring considerable economic and mental burden to society and families, and represent a public health problem requiring urgent attention. Brain-derived neurotrophic factor (BDNF) plays an important role in supporting survival, differentiation, growth, and synapse formation of neurons and participates in the plasticity of nerves. However, it is difficult for BDNF to penetrate the blood-brain barrier (BBB) due to its large molecular weight. Low-frequency focused ultrasound (FUS) combined with microbubbles (MBs) has been demonstrated to be a promising method for opening the BBB non-invasively, transiently, and locally. Here, we studied the therapeutic effect of FUS combined with BDNF plasmid-loaded cationic microbubbles (BDNFp-CMBs) in a rat model of autism. BDNF-CMBs were prepared and the transfection efficiency of FUS combined with BDNF-CMBs was tested in vitro. A rat model of autism was established from the juvenile male offspring of female Sprague-Dawley (SD) pregnant rats treated with sodium valproate (VPA) solution through intraperitoneal injection. The autism rats were randomized into three groups: the VPA group, the BDNFp group, and the FUS + BDNFp-CMBs group. Age-matched normal rats served as the control group (Con). Following treatment, stereotyped, exploratory, and social–behavioral tests were performed on the animals in each group. The rat brains were then collected for subsequent histological examination, and the changes in synaptic structures in the prefrontal cortex were detected under transmission electron microscopy. The results showed that FUS combined BDNFp-CMBs could effectively and non-invasively open the BBB of rats. The stereotyped, exploratory, and social behaviors of the FUS + BDNFp-CMBs group were significantly improved. Compared to the VPA group, the abnormality of neuronal morphology and number in the prefrontal cortex of the FUS + BDNFp-CMBs was alleviated to a certain extent and was accompanied by restoration of the damaged synapses in the encephalic region. Our work demonstrates the positive therapeutic effect of BDNF delivered by FUS non-invasively across the BBB into the prefrontal cortex in a rat model of autism, offering a potential strategy for treating autism.